2019
DOI: 10.5114/aoms.2017.72406
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept protects ovarian reserve against ischemia/reperfusion injury in a rat model

Abstract: Introduction Etanercept has been widely used in autoimmune diseases for blocking tumor necrosis factor α (TNF-α), which is an inflammatory cytokine. The anti-apoptotic and anti-inflammatory effects of etanercept against ischemia/reperfusion (I/R) injury have been shown for several tissues in rat studies, but to the best of our knowledge, there are no reports on its protective effects following similar injury in ovarian tissue. The aim of this study was to investigate whether etanercept has benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 28 publications
7
23
0
Order By: Relevance
“…29 Previous studies have demonstrated that I/R injury aggravates oxidant injury in the ovarian tissue, causing significantly reduced GSH levels; which eventually contribute to cellular injury. 12,30 A similar study by Yayla et al demonstrated a significant reduction in the GSH level in the ovarian tissue after I/R in the case group. 31 We observed similarly reduced GSH levels in the I and I/R groups in our study parallel to the results of previous studies discussed above.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…29 Previous studies have demonstrated that I/R injury aggravates oxidant injury in the ovarian tissue, causing significantly reduced GSH levels; which eventually contribute to cellular injury. 12,30 A similar study by Yayla et al demonstrated a significant reduction in the GSH level in the ovarian tissue after I/R in the case group. 31 We observed similarly reduced GSH levels in the I and I/R groups in our study parallel to the results of previous studies discussed above.…”
Section: Discussionmentioning
confidence: 56%
“…10 Previous studies identified many agents with antioxidant effects, preventing oxidative stress caused by ischemia and reperfusion (I/R) injury in the ovary. 11,12 In addition, the levels of tumor necrosis factor-alpha (TNF-α) and other proinflammatory cytokines increase in reperfusion injury; suggesting that anti-inflammatory agents can be involved more effectively in the prevention of ischemic damage compared to antioxidants. From this point of view, nebivolol (NEB) can be a promising therapeutic agent as it has been displayed to have antiinflammatory and anti-apoptotic effects besides its antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 In ovarian I/R injury, all or part of the blood circulation may be temporarily blocked in surgical interventions, especially caesarean section, or in traumatic events. 27 Although ovarian damage has occurred during ischemia, it has been shown in previous studies that the main damage takes place during reperfusion. 28 In line with the results of previous studies, the results of this study show that reperfusion increases the harmful eff ects of ischemic damage because of migration of active neutrophils and ROS formation.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress reduction has been reported to prevent injury of myocardial tissues [21], and the results of our study also show that treatment with mRNA-103 inhibitor reduces the increased level of oxidative stress. Myocardial infarction occurs due to hypoxia to the myocardial tissues, which activates the apoptosis pathway and increases the apoptosis of myocardiocytes [22][23][24][25]. Apoptosis of myocardiocytes contributes to the degeneration of myocardial tissues, which leads to MI.…”
Section: Discussionmentioning
confidence: 99%